Caracterização comportamental e neuropatológica em modelo de epilepsia do lobo temporal por aplicação intracerebral de pilocarpina em ratos wistar - Andrade, Bruna de Faria Dutra (2017)
Temporal Lobe Epilepsy (TLE), the most frequent focal epilepsy among adults, is characterized by neuronal loss in limbic structures such as the hippocampus and amygdala. Electrophysiological studies have shown that the application of pilocarpine in amygdala of rats induces Status Epilepticus (SE). However, there is no data yet available on the behavioral characteristics of SE induced by intra-amygdalar application of pilocarpine as well as on the effect of this SE on the behavior and morphology of limbic structures. Studies using models of application of kainic acid or electrical stimulation in the amygdala suggest that this structure, besides being susceptible to epileptic seizures, may be involved in the development of chronic disease. Objective: To characterize the acute and chronic behavioral and neuropathological alterations occurring after SE induction by the application of pilocarpine in the amygdala of adult Wistar rats. Material and Methods: Adult and male Wistar rats (total N = 32) were used. A cannula was implanted in the right amygdala of the animals and after one week pilocarpine was applied for SE induction (0,9 mg/uL, SE group, N= 18) or saline solution (1 ul, Ctrl group, N = 14) in the amygdala. Rats were treated 4 hours after SE-onset with diazepam (10mg / kg, i.p). Afterwards, the animals were randomly assigned to two groups characterized according to the time of study after SE onset and euthanasia: 24h and 30 days. The behavior of all animals was recorded by video since the intra-amygdala injections up to 24 hours (group 24h) and 30 days (group 30 days). At the end, brains were paraffin-processed, sectioned and stained with Hematoxylin-Eosin (HE) and Fluoro-Jade C (FJC) for counting of normal and degenerating neurons, respectively. Results: 1) Injection of pilocarpine into the amygdalo-piriform region of Wistar rats induced SE in 100%; 83.3% of the animals had SE with predominantly generalized seizures (Racine≥3); 2) 100% of the animals in the chronic group displayed predominantly partial Spontaneous Recurrent Seizures (SRS); 3) The number of generalized SRSs was dependent on the severity and duration of SRS, occurring very frequently in four of the seven animals evaluated; 4) The number of partial and generalized SRSs defined the degree of neuronal lesion in general. 5) Neuronal lesion - including degeneration and neuronal loss - was found in the amygdala nuclei (cortical and medial lateral, predominantly - LaVM, MePV and PMCo), dorsal endopriform nuclei (Den), thalamus nuclei (predominantly medial, paraventricular and parvicellular nuclei - PVP, MDM, VM and VPPC) and hypothalamus (posterior only, pre-mammillary ventral nucleus - PMV) and peririnal (lateral and medial portions) and piriform cortices (lateral and medial portions). Conclusion - Injection of pilocarpine into the amygdala of Wistar rats induces SE, epilepsy and neuropathological injury of limbic structures, similar to human ELT.